Penegakkan Hukum dan Pertanggung Jawaban Pidana terhadap Kasus Penganiayaan yang Dilakukan Anak di Bawah Umur - Hafipah Tusyadiah; Daffa Amanullah Supriyatno; Najwa Maulida; Muhammad Agung Suryatman; Herli Antoni (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
The goal of this study is to get a better understanding of the legal framework that governs compounding significant crimes against children, as well as some of the legal safeguards accessible to minors who commit major crimes. The three major categories of legal basis employed in normative legal studies that lead to the founding of this publication are primary legal material, secondary legal material, and tertiary legal material. The primary goal of this legal research is to undertake a literature review; as a result, applicable and relevant statutes will be examined and diverted more fullyAccording to the research findings, juveniles who commit severe crimes may face criminal penalties based on their acts or offenses under Law No. 11 of 2012. Only Article 69 paragraph (2) and Article 81 can be used to punish adolescents who commit crimes. Children are legally protected under Law Number 35 of 2014 amending Law Number 23 of 2002 concerning Child Protection. Child protection refers to all efforts made to safeguard and maintain children's rights, including their ability to develop and interact with the world in line with their human dignity and moral ideals, as well as to protect them from harm and damage.